Human Resource Related Disclosures of Malaysian Public Listed Companies - Teh, Caroline Swee Gaik (2004)
Corporate social responsibility has been a phenomenon in the business world for the past few decades considering the amount of studies that have been done. It can be defined as “the impact of a company’s activities on the welfare of a society”. Corporate social responsibility has also been considered to be a company’s commitment to contribute ethically towards economic progress while at the same time improving the lives of their workforce and their families. Generally, engaging in the area of corporate social responsibility would mean being accountable towards human resources, environment, community, products and consumers. With the practice of corporate social responsibility comes the need for corporate social reporting. Over the years, corporate social reporting has gradually increased amongst companies and stakeholders have also demanded for more reporting from companies. This has led to expectations on the extent and form of corporate social disclosures in the annual reports of companies. Human resource has been one area where little in-depth research has been done in terms of the nature of its disclosures. As such, this research intends to examine the voluntary corporate disclosures relating specifically to human resource in Malaysia. In this research, the method of content analysis has been employed to classify and quantify the human resource disclosures in the annual reports of the top 30 companies in Malaysia. It is hoped that this will provide some understanding about the current state of human resource disclosures among Malaysian companies.